Evaluation of pharmacological and pharmacokinetic herb-drug interaction between irinotecan hydrochloride injection and Kangai injection in colorectal tumor-bearing mice and healthy rats - Chen, Yanfei; Hu, Zhaoliang; Jiang, Jing; Liu, Chenxi; Gao, Shuxiao; Song, Min; Hang, Taijun (Frontiers in Pharmacology, 2023)
Introduction: Kangai (KA) injection, a Chinese herbal injection, is often used in combination with irinotecan (CPT-11) to enhance the effectiveness of anti-colorectal cancer treatment and alleviate side effects. However, the combined administration of this herb-drug pair remains controversial due to limited pre-clinical evidence and safety concerns. This study aimed to determine the pre-clinical herb-drug interactions between CPT-11 and KA injection to provide a reference for their clinical co-administration. Methods: In the pharmacological study, BALB/c mice with CT26 colorectal tumors were divided into four groups and treated with vehicle alone (0.9% saline), CPT-11 injection (100 mg/kg), KA injection (10 mL/kg), or a combination of CPT-11 and KA injection, respectively. Tumor volume of mice was monitored daily to evaluate the therapeutic effect. Daily body weight, survival rate, hematopoietic toxicity, immune organ indices, and gut toxicity were analyzed to study the adverse effects. Healthy Sprague-Dawley rats in the pharmacokinetic study were administered KA injection only (4 mL/kg), or a combination of CPT-11 injection (20 mg/kg) and KA injection, respectively. Six key components of KA injection (oxymatrine, matrine, ginsenoside Rb1, Rg1, Re, and astragaloside IV) in rat plasma samples collected within 24 h after administration were determined by LC-MS/MS. Results: The pharmacological study indicated that KA injection has the potential to enhance the anti-colorectal cancer efficacy of CPT-11 injection and alleviate the severe weight loss induced by CPT-11 injection in tumor-bearing mice. The pharmacokinetic study revealed that co-administration resulted in inhibition of oxymatrine metabolism in rats, evidenced by the significantly reduced Cmax and AUC0-t of its metabolite, matrine (p < 0.05), from 2.23 ± 0.24 μg/mL to 1.38 ± 0.12 μg/mL and 8.29 ± 1.34 μg·h/mL to 5.30 ± 0.79 μg·h/mL, respectively. However, due to the similar efficacy of oxymatrine and matrine, this may not compromise the anti-cancer effect of this herb-drug pair. Discussion: This study clarified the pre-clinical pharmacology and pharmacokinetic benefits and risks of the CPT-11-KA combination and provided a reference for their clinical co-administration.